2004
DOI: 10.1213/01.ane.0000139351.40608.05
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Selective Spinal Anesthesia with Hyperbaric Bupivacaine and General Anesthesia with Desflurane for Outpatient Knee Arthroscopy

Abstract: In this randomized and controlled trial, 64 adult ambulatory knee arthroscopy patients received either selective spinal anesthesia (SSA) with 4 mg of hyperbaric bupivacaine or general anesthesia (GA) with desflurane. We conducted the study to determine whether SSA with small-dose bupivacaine provides equal fast-tracking possibilities, a shorter stay in the postanesthesia care unit, and earlier discharge home compared with GA with desflurane. Patients with a high risk for postoperative nausea and vomiting recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 20 publications
3
49
0
2
Order By: Relevance
“…Korhonen et al 12 . compared two groups of patients received either 4mg hyperbaric bupivacaine or propofol-desflurane and determined mean of time for being ready to discharge as 112 and 107 minutes, respectively.…”
Section: Cumhuriyet Medical Journalmentioning
confidence: 99%
“…Korhonen et al 12 . compared two groups of patients received either 4mg hyperbaric bupivacaine or propofol-desflurane and determined mean of time for being ready to discharge as 112 and 107 minutes, respectively.…”
Section: Cumhuriyet Medical Journalmentioning
confidence: 99%
“…Poor postoperative analgesia may effect mobilization, duration of discharge, patient satisfaction, morbidity and mortality. The studies evaluating the effects of regional anesthesia (RA) on functional outcome after TKA were conducted [35][36][37][38][39]. The results of some studies have suggested that Regional anesthesia seems to improve the outcome of patients undergoing total hip or knee replacement when compared with general anesthesia [36].…”
Section: Knee Surgerymentioning
confidence: 99%
“…Either general or epidural anesthesia provide satisfactory anesthesia for outpatient knee arthroscopy and the choice of anesthetic technique may be primarily dependent on the patient's desire to be alert and participatory during the surgical procedure. In another study, Korhonen et al [39] compared selective spinal anesthesia (SSA) with bupivacaine and general anesthesia with desfluran for outpatient knee arthroscopy. The goal of this study was to assess whether SSA with small-dose hyperbaric bupivacaine provides an equal possibility of fast-tracking, a shorter stay in the postanesthesia care unit (PACU), and earlier discharge home compared with GA with desflurane.…”
Section: Knee Surgerymentioning
confidence: 99%
“…Regional anesthesia is an alternative method to general anesthesia. It has been demonstrated that regional anesthesia significantly reduces the morbidity by decreasing the occurrence of deep vein thrombosis, pulmonary embolism, transfusion requirement, pneumonia, depression of respiration, myocardial infarction, and renal failure (2,3). Bradycardia, which occurres below the block level in the regional anesthesia, and develop by the vasodilatation-induced hypotension, and sympathetic denervation, can increase the severity of the condition of patients especially with cardiac problems or elderly people (4).…”
Section: Introductionmentioning
confidence: 99%